Tourism, Development, and Poverty Eradication: Is It Possible? - Carranza-Benites, Renzo J. (2025)
Tourism, as a social and economic phenomenon, is inextricably linked to the structural conditions of proverly in the territory where it takes place. It is not merely an economic driver; it involves a transformation of inequalities, making visible the tension between development, exclusion, and the pursuit of well-being. This implies that, in the analysis of poverty from the perspectve of toursm, variables from psychology and sociology must be introduced to understand how experiences of poverty shape subjectivities, motivations, and identies. Therefore, the review of the chapter challenges even the conceptual framework needed to address tourism in contexts of poverty, as well as the theoretical approach it presents. It is striking to recognize that tourism in situations of poverty or inequality cannot be separated from the psychosocial practices that generate senses of belonging, aspiration, and perceptions of well.being.